معيقات الرياضة المدرسية ( النشاط اللاصفي ) في الطور الإبتدائي - دحماني, سعاد (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
معيقات الرياضة المدرسية "النشاط اللاصفي" في المرحلة الابتدائية وتهدف الدراسة إلى محاولة معرفةمعيقات الرياضة المدرسية "النشاط اللاصفي" في المرحلة الابتدائية،حيث تكونت عينة الدراسة من 50 أستاذ واستاذة في الطور الابتدائي، وتم اختيارها بطريقة قصدية، بنسبة 15 بالمئة من مجتمع البحث، واستعملنا أداة الاستبيان، واستخدمنا وجاءت أهم نتائج الدراسة ان الوسائل المتواجدة داخل المنشآت الرياضية غير كافية لجميع التلاميذ حين ممارستهم لبعض الأنشطة الرياضية، وان الملاعب المتواجدة في المدارس الابتدائية لا تتوفر على عوامل الامن والسلامة للتلاميذ لممارسة الأنشطة الرياضية اللاصفية، اما اهم الاقتراحات والتوصيات فتمثلت بداية بضرورة الاهتمام بالجمعيات الثقافية للرياضة المدرسية وإعادة بعثها وإعطائها الأهمية والدور الموكل لها، والتنسيق بين مختلف الهيئات المشرفة على الرياضة المدرسية وذلك لتنظيم برامج الرياضة المدرسية وإعادةبعثها من جديد. // // // // // Obstacles to school sports “extracurricular activity” in the primary stage The study aims to try to find out the obstacles to school sports (extracurricular activity) in the primary stage. The study sample consisted of 50 male and female teachers in the primary stage, and it was chosen intentionally, at a rate of 15 percent of the research community. We used the questionnaire tool, and the most important results of the study were that The means available within sports facilities are not sufficient for all students when they practice some sports activities, and the playgrounds in primary schools do not have security and safety factors for students to practice extracurricular sports activities. As for the most important suggestions and recommendations, they initially represented the necessity of paying attention to cultural associations for school sports, reviving them and giving them importance and role. entrusted to it, and coordination between the various bodies supervising school sports in order to organize school sports programs and revive them again.
MEPS-2024-35
Keywords: الرياضة المدرسية - المرحلة الابتدائية // // : school sports - primary stage